2018
DOI: 10.37828/em.2018.16.8
|View full text |Cite
|
Sign up to set email alerts
|

First Record of Round Goby Neogobius Melanostomus pallas, 1814 (Pisces: Gobiidae) in Bosnia and Herzegovina

Abstract: This paper gives the first record of round goby Neogobius melanostomus Pallas, 1814 (Pisces: Gobiidae) in Bosnia and Herzegovina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…Our review of the literature showed that the freshwater gobies of Bosnia and Herzegovina includes six genera with seven species. In contrast with earlier publications (Vuković 1963, 1977, Bogut et al 2006, Sofradžija 2009, the present study lists four new species (B. gymnotrachelus, K. radovici, O. croaticus and N. melanostomus), reflecting developments in ichthyological research, the description of species new to science (Kovačić 2005) and the expansion of invasive species (Delić et al 2014, Nedić et al 2014, Čolić et al 2018. The absence of certain species is also verified, and recent scientific evidence forces us to exclude four species from the current checklist: K. panizzae, which is likely a misidentification (for details, see Kovačić &Pallaoro 2003 andKovačić 2009); P. microps considering Kottelat & Freyhof (2007) and Šanda & Kovačić (2009); P. marmoratus given the new findings from molecular studies that show it only inhabits marine and brackish water (Stepien & Tumeo 2006, Neilson & Stepien 2009a, and Z. ophiocephalus for which there was never confirmed evidence of its occurrence.…”
Section: Overview Of the Available Literaturecontrasting
confidence: 74%
See 3 more Smart Citations
“…Our review of the literature showed that the freshwater gobies of Bosnia and Herzegovina includes six genera with seven species. In contrast with earlier publications (Vuković 1963, 1977, Bogut et al 2006, Sofradžija 2009, the present study lists four new species (B. gymnotrachelus, K. radovici, O. croaticus and N. melanostomus), reflecting developments in ichthyological research, the description of species new to science (Kovačić 2005) and the expansion of invasive species (Delić et al 2014, Nedić et al 2014, Čolić et al 2018. The absence of certain species is also verified, and recent scientific evidence forces us to exclude four species from the current checklist: K. panizzae, which is likely a misidentification (for details, see Kovačić &Pallaoro 2003 andKovačić 2009); P. microps considering Kottelat & Freyhof (2007) and Šanda & Kovačić (2009); P. marmoratus given the new findings from molecular studies that show it only inhabits marine and brackish water (Stepien & Tumeo 2006, Neilson & Stepien 2009a, and Z. ophiocephalus for which there was never confirmed evidence of its occurrence.…”
Section: Overview Of the Available Literaturecontrasting
confidence: 74%
“…Though gobies are a large and widespread family that have radiated into marine, brackish and inland waters of tropical and temperate regions (Nelson 2006, most of the documented knowledge of their presence and distribution in Bosnia and Herzegovina consist of recycled comments from general reviews and species lists, without the support of specific evidence of specimens caught (Vuković 1963, 1977, Bogut et al 2006, Sofradžija 2009 and typically with little new information (Šanda & Kovačić 2009, Delić et al 2014, Nedić et al 2014, Čolić et al 2018. With the exception of Šanda et al (2008) and Šanda & Kovačić (2009), who were the first to provide a detailed critical review of the occurrence and geographical and ecological distribution of freshwater gobies within the Adriatic Sea catchment, others have avoided critical re-evaluation of the status and presence of gobies, potentially making their reports unreliable.…”
Section: Overview Of the Available Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…According to Piria et al (2018) fish introductions represent a serious threat for stability of native freshwater ecosystems and biodiversity, especially in areas with high biodiversity and endemism, such as the many water bodies in the Balkans. However, more than 20 alien freshwater fish species were introduced in Bosnia and Herzegovina since the beginning of the 20th century (Piria et al 2018;Ĉolić et al 2018).…”
mentioning
confidence: 99%